Logbook: experience of teaching-learning management and management in nursing and health - José Luís Guedes dos Santos; Aline Lima Pestana; Patrícia Guerrero; Patrícia Klock; Alacoque Lorenzini Erdmann (Universidade Federal do Ceará, 2013)
The article aimed at reporting an experience of a group of post-graduate students in teaching on the stage of implementation active teaching-learning methodologies in the discipline of Management in Nursing and Health. The experience happened in three different admission units of a federal hospital in the southern region of the country, in the second semester of 2010. We used a logbook for students to register the journey to deepen the reflections on the experiences of the actions of management. At the end of the internship, the students were asked the logbook so that experiences, feelings, anxieties generated in the course of the journey to knowledge could be identified. The students report that the curricular internship of Management in Nursing and Health is a process of construction that gradually allows to have a sense of what awaits them when they are professionals, thus contributing to a critical and reflective formation.